Azithromycin Nanosuspension Preparation using Evaporative Precipitation into the Aqueous Solution (EPAS) Method and its Comparative Dissolution Study - Shariare, Mohammad H.; Mondal, Tonmoy Kumar; Alothaid, Hani; Sohel, Md. Didaruzzaman; Wadud, Md.; Aldughaim, Mohammed S.; Rashid, Md Abdur; Kazi, Mohsin (Current Pharmaceutical Analysis, 2021)
Aim: EPAS (evaporative precipitation into aqueous solution) was used in the current studies to prepare azithromycin nanosuspensions and investigate the physicochemical characteristics for the nanosuspension batches with the aim of enhancing the dissolution rate of the nanopreparation to improve bioavailability. Methods: EPAS method used in this study for preparing azithromycin nanosuspension was achieved through developing an in-house instrumentation method. Particle size distribution was measured using Zetasizer Nano S without sample dilution. Dissolved azithromycin nanosuspensions were also compared with raw azithromycin powder and commercially available products. The total drug content of nanosuspension batches was measured using an Ultra-Performance Liquid Chromatography (UPLC) system with Photodiode Array (PDA) detector while residual solvent was measured using Gas Chromatography (GC). Results: The average particle size of azithromycin nanosuspension was 447.2 nm and total drug content was measured to be 97.81% upon recovery. Dissolution study data showed a significant increase in the dissolution rate for nanosuspension batch when compared to raw azithromycin and commercial version (microsuspension). The residual solvent found for azithromycin nanosuspension is 0.000098023 mg/mL or 98.023 ppb. Conclusion: EPAS was successfully used to prepare azithromycin nanoparticles that exhibited a significantly enhanced dissolution rate. Further studies are required to scale up the process and determine long term stability of the nanoparticles.
Keywords: Azithromycin nanoparticles